Effect of creep phenomena on room-temperature tensile properties of cast & forged P91 steel. (September 2017) - Pandey, Chandan; Mahapatra, M.M.; Kumar, Pradeep; Saini, N.
Abstract: In present research work, the as-received cast & forged (C&F) P91 steel was subjected to the creep test at temperature of 620 °C and 650 °C for applied stress of 120 MPa. The room temperature tensile test was conducted after normalizing and tempering (N&T) treatment of the ruptured creep specimen. The standard tensile-test specimen was prepared from the gauge section of creep ruptured specimen. The N&T treatment was performed to restore the microstructure and mechanical properties of virgin P91 steel (N&T P91 steel). The microstructure of creep fractured specimen in ruptured state and N&T condition were characterized by using field-emission scanning electron microscope (FE-SEM) with energy dispersive X-ray spectroscopy (EDS). The fracture surface morphology of crept specimen and the tensile tested specimen was also studied. The effect of prior creep deformation on the mechanical strength was more significant in the sample with longer creep rupture life. Highlights: Creep test was performed in temperature range of 620 o C-650 o C at stress of 120 MPa. Study the effect of creep rupture life on precipitate size and fraction area of precipitates. Study the effect of creep rupture life on fracture surface morphology of creep tested cast-forged P91 steel. The tensile properties of N&T creep fractured material compared with N&T cast-forged P91 steel. Study the fracture surface morphology of tensile fractured surface by using FESEM.